RELATIONSHIP BETWEEN THE LONGEST OF DIABET 2 TYPE WITH PLASMA BLOOD SUGAR LEVELS IN PATIENTS WITH MELITUS TYPE 2 DIABETS - Maay, Jems KR; Rumaseb, Ester; Apay, Frengki; Ngardita, Ray (International Journal of Psychosocial Rehabilitation, 2020)
Diabetes mellitus (DM) is a chronic disease that occurs when the pancreas produces insufficient amounts of insulin or if the body cannot use insulin effectively. WHO estimates that DM causes about 60% of deaths and 40% of illness worldwide (Maulana, 2009). Indonesia ranks 4th (four) with the largest number of people with DM in the world after India (19%), China (16%), and the United States (13.9%). The prevalence of DM in Indonesia in 2025 is 12.4 million people, has doubled compared to 1945 which was 4.5 million people (Maulana, 2009). According to Suyono (2006), the increase in the number of DM sufferers globally is due to an increase in prosperity and lifestyle changes. The prevalence of DM sufferers in Indonesia in 2000 was 8.4 million people and is expected to increase to21.3 million in 2030 (PERKENI, 2006). According to basic health research (2013) conducted in Indonesia, the prevalence of DM in several areas including Jakarta the prevalence of 2.5%, West Java the prevalence of 1.3%, in East Java the prevalence of 2.4%, the prevalence of DM in Yogyakarta 2.6 %, North Sulawesi prevalence is 2.4%, Central Kalimantan is 2.3%, Bangka Belitung has a prevalence of 2.1%, Lampung has a prevalence of 0.7%, and Papua Province has a prevalence of 0.8%. While research that has been done in China some time ago, if someone in his life lacks physical exercise or sports, then glycogen or fat reserves will remain stored in the body, this is what triggers various degenerative diseases, for example, type II diabetes mellitus (Yunir and Soebardi, 2008). Research on the relationship between long-suffering with plasma blood sugar levels in patients with type 2 diabetes has not been widely studied in Papua. The number of people with type 2 diabetes in Papua is quite high.